Islamic Education Teachers' Strategy for Integrating Digital Technology in the Learning Process at MTsS Diponegoro Mendiro - Muhammad Abid Al Khilmi; Mutohharun Jinan (Journal of Educational Sciences, 2026)
Study This focuses on the PAI Teacher Strategy to integrate Digital Technology in the Islamic Religious Education Learning Process at MTsS Diponegoro Mendiro . The purpose of study is analyze the strategies used by PAI teachers to integrate digital technology in the learning process . This method chosen in a way qualitative with There are 3 types of data collection processes that is interviews , observations , and documentation towards Islamic Education Teachers and students . Findings study This prove that  Islamic Education teachers use some strategies for integrate digital technology to in the PAI learning process , as as follows : 1) First , the E-Learning Platform , namely make it easier for teachers and students For Study more easy 2) Second , Interactive Digital Module is convey a number of material For interesting attention 3 ) Third , Google Drive and Google Form are presented For list storage a number of material . However , in implementing this strategy , Islamic Education teachers and students experience constraint in adjustment . This strategy have objective For optimize to stay relevant and positive influence to integration digital technology to Islamic Education teachers and students